Limited proficiency English teachers’ language use in science classrooms - Asiah Mohd Sharif, (Penerbit UKM, 2013)
The English for Teaching Mathematics and Science (ETeMS) policy was reversed in 2012 citing the reason that about 40% of the teachers were still using Malay in the ETeMS classroom hence, affecting the successful implementation of ETeMS. The quality of English used by the 60% and the other 40% especially in the rural areas motivates this study. Data for this investigation was obtained from three English teachers who have limited proficiency. These limited English proficiency (LEP) teachers teach science through English in a rural primary school in Malaysia. Transcripts of nine lessons, classroom observations and teacher interviews were gathered. The findings reveal that the English language used by the LEP teachers was simple and frequently riddled with errors which resulted in distortion of content taught. Errors were linked to negative transfers from Bahasa Melayu, teachers’ interlanguage, unsuccessful guesswork and memorizing words without full understanding of meaning. The LEP teachers therefore, made poor models for their students. The researcher concludes that even if the LEP teachers had striven to teach completely in English, the policy may have been seen to be implemented, but the quality of classroom discourse and content taught would have been problematic.